A first test of focusing theory - Markus Dertwinkel-Kalt; Gerhard Riener (University of Mannheim, Department of Economics, 2016)
Focusing theory hypothesizes a bias toward concentration according to which consumers prefer goods with one outstanding feature over those with several smaller sized upsides. In contrast to models of present-biased behavior, focusing theory prescribes also future-biased behavior if an option's future reward is particularly outstanding. Our laboratory experiment yields substantial support for the bias toward concentration and finds both present-biased and future-biased choices as predicted by focusing theory.
urn:nbn:de:bsz:180-madoc-408401
Keywords: D03; D11; D90; 330; Attention; Focusing; Rational choice